On the microstructure properties correlation of the recycled aluminium alloy - Noah Arputharaj, Nhanam (2016)
This study relates with recycled aluminium alloy. Aluminium is the third most abundant element on earth. It is widely used in aerospace and automobile industry. However, aluminium used mostly in industry are recycled aluminium. This is because recycled aluminium only needs 5% of energy needed compared to energy needed to produce aluminium from its ore. Unfortunately, recycling of aluminium generates secondary aluminium which is high in Fe content. Presence of Fe lowers ductility and tensile strength on aluminium. Iron increases the porosity in aluminium alloy. This is due to the presence of brittle β-Al5FeSi Needle structure in high Fe content recycled aluminium alloy. The motive of this study is to reduce the presence of brittle β-Al5FeSi Needle structure by inoculation method. The innoculation elements are Nickel and Chromium. The objective of this study is to conduct melting and casting experiments of recycled aluminium, to study the effect of heat treatment on aluminium alloy, to study the microstructure properties of aluminium alloy by innoculation and to study the tensile strength of aluminium alloy. From the result of this study, 1.0% of Ni is the best innoculation percentage for as-cast alloy, 2.0% of Ni is the best innoculation percentage for heat treated alloy, 2.0% of Cr is the best innoculation percentage for as-cast alloy and finally 2.0% of Cr is the best inoculation percentage for heat treated alloy.